Peningkatan Kesadaran Studi Lanjut Masyarakat Perantau melalui Seminar Pendidikan - Rosyidi, Moh. Alfin; Jinan, Anisatul; Alami, Rahmalina; Sutrisno, Tri (Kifah: Jurnal Pengabdian Masyarakat, 2024)
This community service program aims to provide a deeper understanding of the importance of continuing higher education. This activity is in the form of a seminar on the importance of raising awareness among the youth of Padike Village, the majority of whom are migrants, about the urgency of continuing their education to college. The PkM collaboration of five campuses, namely IAIN Madura, UINSA, UINSUKA, Annuqoyah University, and UIM Pamekasan, has achieved quite good results. This activity uses the Participatory Action Research (PAR) method. The results are in the form of an increase in the perception of the importance of college from 21% to 89%. This data indicates that the seminar was successful in increasing participants' awareness and interest in higher education, and had a significant positive impact in changing their attitudes towards the importance of continuing their education to a higher level.